Access to Capital and Regeneration of Young Farmers in Kintamani Village - Paramaartha, I Made Ary; Harsanto, Budi; Yunizar, Yunizar (LifeSciFi, 2026)
Access to capital is a crucial factor in the sustainability of the agricultural sector, especially in production centers such as Kintamani, Bali. This study aims to explore farmers’ accessibility to Microfinance Institutions (MFIs), its impact on their welfare, as well as its implication on the interest of regeneration. Welfare, as well as its implication on young farmers’ regeneration interest. This research uses a qualitative method with a case study approach in Kintamani. Data were collected through in-depth interviews with 21 informants consisting of farmers, farmers group association/LKM administrators, village government, and the younger generation, as well as field observations. Field observation. The results showed a dualism of access to capital where traditional farmers prefer the informal sector (middlemen) because of the ease of procedures (zero admin) and speed of liquidity compared to formal MFIs. Speed of liquidity compared to formal MFIs. In terms of welfare, the existing access to capital has not been able to become a significant economic leverage and only functions as a safety net in a cycle of “digging holes closing holes”. Transformation is needed institutionalization of Farmers Group Association into an off-taker and modernization of technology to re-attract the younger generation.